Charging Stations vs. Battery Swapping Stations Considering Battery-to-Grid Injections - Cihan Guldorum, Hilmi; Diaz-Cachinero, Pablo; Munoz-Delgado, Gregorio; Contreras, Javier (IEEE, 2024)
Battery swapping stations (BSSs) have been increasingly attracting the attention of researchers. The advantages of BSS over conventional charging stations (CS) have not been sufficiently investigated. In this work, an optimization model for the BSS operation that aims to maximize its revenue is proposed. Charging and discharging management is allowed by considering time-varying electricity tariffs and by taking part in ancillary services to the grid via battery-to-grid. In addition, photovoltaic (PV) power generation is considered in the proposed approach. The social effects of the proposed optimization model are investigated by examining the comfort effect for each EV owner. Additionally, the proposed model for the operation of a BSS is compared to a conventional CS model, in which the swapping feature is disregarded. The proposed model is developed in the form of mixed-integer linear programming (MILP) and solved using the CPLEX solver in the General Algebraic Modeling System (GAMS) environment. The findings revealed that BSS outperformed CS in terms of profits.
Keywords: Battery swapping station; battery-to-grid; electric vehicle; mixed-integer linear programming; vehicle-to-grid; Computer Science; Science & Technology - Other Topics; Energy & Fuels; Engineering